
急急急!!数学高手进来!!
-3^4-4÷4/9×(-9)-1[1-(1-0.5)×4^3)](-1)^3÷(-2/9)+2^2×(-0.5)^2-4×(-2)^3-(-1))^101÷0.5要算式...
-3^4 -4 ÷ 4/9 × (-9)
-1[ 1-(1-0.5)× 4^3) ]
(-1)^3 ÷ (-2/9) + 2 ^2 ×(-0.5)^2
-4 × (-2)^3 -(-1))^101 ÷ 0.5
要算式 展开
-1[ 1-(1-0.5)× 4^3) ]
(-1)^3 ÷ (-2/9) + 2 ^2 ×(-0.5)^2
-4 × (-2)^3 -(-1))^101 ÷ 0.5
要算式 展开
1个回答
展开全部
-3^4 -4 ÷ 4/9 × (-9)
=-81+16
=-65
-1[ 1-(1-0.5)× 4^3) ]
=-(1-0.5×64)
=-(1-32)
=31
(-1)^3 ÷ (-2/9) + 2 ^2 ×(-0.5)^2
=1×9/2+4×0.25
=9/2+1
=11/2
-4 × (-2)^3 -(-1))^101 ÷ 0.5
=4×8-(-1)÷0.5
=32+2
=34
=-81+16
=-65
-1[ 1-(1-0.5)× 4^3) ]
=-(1-0.5×64)
=-(1-32)
=31
(-1)^3 ÷ (-2/9) + 2 ^2 ×(-0.5)^2
=1×9/2+4×0.25
=9/2+1
=11/2
-4 × (-2)^3 -(-1))^101 ÷ 0.5
=4×8-(-1)÷0.5
=32+2
=34
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询